Neurodevelopmental disorders in children born to mothers with systemic lupus erythematosus. (October 2014) - Vinet, É; Pineau, CA; Clarke, AE; Fombonne, É; Platt, RW; Bernatsky, S
Children born to women with systemic lupus erythematosus seem to have a potentially increased risk of neurodevelopmental disorders compared to children born to healthy women. Recent experimental data suggest in utero exposure to maternal antibodies and cytokines as important risk factors for neurodevelopmental disorders. Interestingly, women with systemic lupus erythematosus display high levels of autoantibodies and cytokines, which have been shown, in animal models, to alter fetal brain development and induce behavioral anomalies in offspring. Furthermore, subjects with systemic lupus erythematosus and neurodevelopmental disorders share a common genetic predisposition, which could impair the fetal immune response to in utero immunologic insults. Moreover, systemic lupus erythematosus pregnancies are at increased risk of adverse obstetrical outcomes and medication exposures, which have been implicated as potential risk factors for neurodevelopmental disorders. In this article, we review the current state of knowledge on neurodevelopmental disorders and their potential determinants in systemic lupus erythematosus offspring.